UNDERSTANDING Portrait Photography : How to Shoot Great Pictures of People Anywhere - Peterson, Bryan, 1952- (California : Watson-Guptill, 2020)
"Great portraits go beyond a mere record of a face. They reveal one of the millions of intimate human moments that make up a life. In Understanding Portrait Photography, renowned photographer Bryan Peterson shows how to spot those "aha!" moments and capture them forever, rather than relying on pure luck and chance. Peterson's approach explains what makes a photo memorable, how to locate the universal themes that everyone can identify with, and how to use lighting, setting, and exposure to uncover the wonder and joy of everyday living
Understanding people -- Working with people -- Light -- Composing powerful portraits.
Includes index
"New & revised edition of Beyond Portraiture."
Keywords: Portrait photography